2016
DOI: 10.5489/cuaj.3687
|View full text |Cite
|
Sign up to set email alerts
|

The effects of previous open renal stone surgery types on PNL outcomes

Abstract: E246Cite as: Can Urol Assoc J 2016;10(7-8) Patients who had a history of ORSS with parenchymal insicion, such as radial nephrotomies, anatrophic nephrolithotomy, lower pole resection, and partial nephrectomy, were included in Group 1. Other patients with a history of open pyelolithotomy were enrolled in Group 2. Preoperative characteristics, perioperative data, stone-free status, and complications were compared between the groups. Stone-free status was defined as complete clearance of stone(s) or presence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the study of Çakici et al 9 and Aydemir et al, 13 the most common stones leading to open surgery were staghorn stones. Other studies by Ozgor et al 11 and El-Husseiny & Buchholz 14 also showed that the most common stones leading to open surgery were staghorn types. Actually, the renal structural changes created by staghorn stones in most cases force the physician to consider surgery to remove the stone.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the study of Çakici et al 9 and Aydemir et al, 13 the most common stones leading to open surgery were staghorn stones. Other studies by Ozgor et al 11 and El-Husseiny & Buchholz 14 also showed that the most common stones leading to open surgery were staghorn types. Actually, the renal structural changes created by staghorn stones in most cases force the physician to consider surgery to remove the stone.…”
Section: Discussionmentioning
confidence: 83%
“…However, in a study by Ozgor et al, this ratio did not show a significant deviation despite the fact that men were still more likely to be candidates for surgery. 11 The reason for the higher prevalence of urinary stones in males may be due to the higher secretion of calcium oxalate and uric acid and less citrate production in men than women, leading to more severe complications. 12 In the present study, almost half of the patients were identified with staghorn stones.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, as with any secondary analysis of an administrative database, it may be prone to coding errors leading to misclassification bias. Thirdly, the retrospective design of our study subjects it to selection bias and unmeasured variables such as prior surgery, 29 obesity, [30][31][32] stone complexity, 33 burden, location of calculi, number of punctures, 34 approach (supine/prone) 35 , exit strategy (tube or tubeless) 36 , and need for secondary procedures, which may impact outcomes and costs. Fourthly, we were only able to capture inpatient hospitalization requiring at least 1 night of hospital stay.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…This method has been successfully applied by urologists in many centers with very high stone-free rates. [4] Ultramini percutaneous nephrolithotomy performed using minimal invasive tools has been applied with success thanks to accumulated PNL experience and the technological developments. [5] So with the experience gained in PNL, ultra-mini percutaneous hepatolithotomy can be used for the treatment in hepatolithiasis cases with high morbidity.…”
Section: Introductionmentioning
confidence: 99%